Peggy Stewart at School - Jackson, Gabrielle E. (Gabrielle Emilie), 1861- (Salt Lake City, UT : Project Gutenberg, 2007)
"Peggy Stewart at School" by Gabrielle E. Jackson is a novel written in the early 20th century. The story centers around Peggy Stewart, a charming fifteen-year-old girl, as she navigates the complexities of adolescence amidst family changes and the arrival of her aunt, Mrs. Peyton Stewart. The plot unfolds in the backdrop of Severndale, Maryland, where traditional familial bonds clash with new dynamics introduced by Peggy$1 (Bs visiting aunt. At the start of the novel, Peggy awakens on a warm September morning, welcoming her aunt, who has come to stay at Severndale. The opening scene highlights the serene yet stifling atmosphere of the household, as old family traditions and relationships are threatened by the aunt's authoritative presence. Through Peggy's eyes, the reader experiences her growing discomfort with her aunt's overbearing nature, gradually feeling the weight of her responsibilities as the mistress of the house. Relationships with family members and the loyal servants, who have cared for her since childhood, become strained, setting the stage for unfolding tensions and conflicts that Peggy must navigate. (This is an automatically generated summary.)s
Release date is 2007-07-20
E-text prepared by Roger Frank and the Project Gutenberg Online Distributed Proofreading Team (https://www.pgdp.net)
Keywords: United States Naval Academy -- Fiction; Young women -- Education -- Fiction; Children of military personnel -- Fiction; Maryland -- Fiction; Washington (D.C.) -- Fiction